COVID-19 risk mitigation in reopening mass cultural events: population-based observational study for the UK Events Research Programme in Liverpool City Region - Burnside, G; Cheyne, CP; Leeming, G; Humann, M; Darby, A; Green, MA; Crozier, A; Maskell, S; O'Halloran, K; Musi, E; Carmi, E; Khan, N; et al. (SAGE Publications, 2023)
Objectives: To understand severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission risks, perceived risks and the feasibility of risk mitigations from experimental mass cultural events before coronavirus disease 2019 (COVID-19) restrictions were lifted.